A VEHICLE ROUTING PROBLEM OPTIMIZATION WITH DRONE USING TABU SEARCH ALGORITHM AND ANALYTICAL HIERARCHY PROCESS - Linda Nuryanti (Majalah Ilmiah Pengkajian Industri, 2021)
This research presents optimization of the fastest route using Drone. Vehicle Routing Problem with Drones (VRPD) is used for planning the mapping of areas with minimal makespan. Drone point route design aims to mapping the area with considering the boundaries. In this paper, an optimization method using the Tabu Search algorithm and Analytical Hierarchy Process (AHP) to resolve VRPD problems is proposed. Tabu Search algorithm is suitable for the implementation of Vehicle Routing Problem because it is able to find the closest distance optimally with guiding other processes using a series of movements to change one solution to another. The optimization process using Tabu Search can find a suitable pair of points so that the closest route can be found. AHP is used for the weighting process and determining the hierarchy of route selection by prioritizing routes that meet the criteria and the appropriate weights. The optimization resulted in a 7.08% reduction in the distance and significantly reduce the makespan as well as the metaheuristic approach. Experimental processes and performance analysis are carried out to find that this method can consistently produce better and optimal solutions. Keywords : Vehicle Routing Problem with Drone; Analytical Hierarchy Process;Tabu Search; Mapping